Noções de escala musical e de seriação operatória em crianças com e sem experiência musical prévia - Rampinelli, Mariella Dalvi (2012)
The present study aimed at investigating the psychogenesis of the notion of musical scale during the concrete operational stage and its possible relationshipwith thenotion of the operational seriation. The research also intended to identify the possible influence of previous musical experience in the construction of the notion of musical scale.18 childrenfrom a private school in Vitória-ESwere subjects of the research: six children were seven years old, other sixwere nine years oldand six were eleven years old.A questionary on the previous musical experience of each participant was used firstlywith the purpose of data collection. After that, it was used the classical Piaget trial to checkthe notion of operational seriation and an adapted test to verify the notion of auditive seriation. Finally, the researcher made a semistructured interview which aimed at detailingthe dataabout the previous musical experience of the participants. The theoreticalbasis for the data collection was the Piaget Clinical Investigation Method.The results of the research showed that the previous musical experience is one of the factors that may influence the acquisition the notion of auditive seriation. Beyond that, it was possible to find outthat the seriation notion can be important for the auditive seriation build up, taking for granted that it ispresent, in different ways, in all participants. In this way, it is expected that this work might contribute to the musical education area when demonstrating the importance of the experience between the subject and the objectfrom the point of view of Piaget’s genetics epistemology, mainly in what refers to music.